2004
DOI: 10.1038/sj.leu.2403518
|View full text |Cite
|
Sign up to set email alerts
|

Both IGH translocations and chromosome 13q deletions are early events in monoclonal gammopathy of undetermined significance and do not evolve during transition to multiple myeloma

Abstract: Molecular and genetic events associated with the transition from monoclonal gammopathy of undetermined significance (MGUS) to multiple myeloma (MM) are still poorly characterized. We investigated serial bone marrow specimens from 11 patients with MGUS who eventually progressed to MM (MM post-MGUS) by interphase fluorescence in situ hybridization for immunoglobulin heavy-chain gene (IgH) translocations and chromosome 13q deletions (del(13q)). In nine patients, IgH translocations were present both in MGUS and MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 21 publications
4
38
0
2
Order By: Relevance
“…7,8 Cytogenetic studies using fluorescence in situ hybridization (FISH) have demonstrated that most genetic lesions typical of MM are already present in MGUS stage. [9][10][11] We recently have shown that a major difference between these three entities is the number of PC with genetic abnormalities, which increases from MGUS to SMM and to MM. 12 It demonstrates that the progression from MGUS to SMM, and eventually to MM, involves a clonal expansion of genetically abnormal PC.…”
Section: Multiple Myeloma (Mm) Is a Malignant Disorder Characterized mentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Cytogenetic studies using fluorescence in situ hybridization (FISH) have demonstrated that most genetic lesions typical of MM are already present in MGUS stage. [9][10][11] We recently have shown that a major difference between these three entities is the number of PC with genetic abnormalities, which increases from MGUS to SMM and to MM. 12 It demonstrates that the progression from MGUS to SMM, and eventually to MM, involves a clonal expansion of genetically abnormal PC.…”
Section: Multiple Myeloma (Mm) Is a Malignant Disorder Characterized mentioning
confidence: 99%
“…The only five cases with no CNA were from asymptomatic entities (two MGUS and three SMM patients), whereas all MM patients showed at least one CNA. Overall, a total of 703 DNA copy number changes were detected with a median of 8 imbalances per abnormal case (range, 1-32 imbalances): 374 gains with a median of 4 per abnormal case (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and 329 losses with a median of 3 (range . A detailed description of the most frequent aberrations is shown in Supplementary Table 2.…”
Section: Quality Assessment Of Snp Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…2 aufgeführten häufigen Partnerloci nachweisen. Insgesamt zeigen etwa 50-70% der MM eine Translokation von 14q32, wobei der ge- [12,17]. Als relativ häufige sekundäre Translokationen finden sich Alterationen des C-MYC-Locus, die in etwa 10-15% unselektierter MM zu finden sind, aber in 50% der Fälle mit plasmablastischer Morphologie sowie häufig in Plasmazellleukämien [2].…”
Section: Zytogenetik Und Molekulargenetik Von Plasmazellneoplasienunclassified
“…Eine häufige numerische Aberration insbesondere bei MM mit Ig-Translokationen sind Deletionen von 13q bzw. die Monosomie 13, die in früheren Studien einen prognostisch ungünstigen Faktor darstellten [13,17]. Eine zweite große Gruppe von MM zeigt einen hyperdiploiden Chromosomensatz mit zusätzlichen Kopien vor allem der Chromosomen 3, 5, 7, 9, [14].…”
Section: Zytogenetik Und Molekulargenetik Von Plasmazellneoplasienunclassified